AIR LEAK SYNDROME IN A NEWBORN WITH RESPIRATORY DISTRESS - CASE REPORT - Naunova Timovska, Silvana; Mandzukovska, Hristina; Voinovska, Tamara; Neskova, Spasija; Vejseli, Besim; Kraljeva, Eva; Gavrilovska, Aleksandra (Journal of Morphological Sciences; Vol 7 No 1 (2024): JMS, 2024)
Air leak syndrome is air accumulation into extra alveolar spaces where it is not normally present, most often resulting from an alveolar rupture with air trapping in the extra pulmonary space. It is more common in neonates with lung diseases such as respiratory distress (RD) or meconium aspiration syndrome (MAS). Air trapping in the extra pulmonary space can create life-threatening conditions by compression of the lung or major blood vessels and the gas exchange or blood flow can be severely compromised. Air leak syndrome includes the clinical presentation of a group of diseases that have a similar pathophysiological mechanism, such as pneumothorax, pneumomediastinum, subcutaneous emphysema, pulmonary interstitial emphysema, pneumopericardium and pneumoperitoneum. Of particular importance has the manifestation of pneumothorax due to the risk of airway collapse, clinical condition call tension pneumothorax. This is a medical emergency that requires immediate medical attention.  We present a premature newborn with respiratory distress and air leak syndrome (pneumothorax, pneumomediastinum and subcutaneous emphysema). Key words: newborn, air leak syndrome, pneumothorax, pneumomediastinum, respiratory distress.